Skeletal phenotypes in postmenopausal women affected by primary hyperparathyroidism - Corbetta, Sabrina; Gianotti, Laura; Castellano, Elena; Carrara, Silvia; Raineri, Francesca; Munari, Elisabetta; Guabello, Gregorio; Cairoli, Elisa; Chiodini, Iacopo; Giovanelli, Luca; Pierotti, Laura; Dinoi, Elisa; et al. (Frontiers in Endocrinology, 2024)
Purpose The current primary hyperparathyroidism (PHPT) presents as a mild disease. We explored skeletal phenotypes in postmenopausal women affected by PHPT, focusing on fractures prevalence. Methods PHPT women were retrospectively evaluated at four Italian centers for osteoporosis management (2 centers in Milan, n=244; Cuneo, n=128; Pisa, n=131). Data collected from clinical records were analyzed by hierarchical clusterization. Results Considering the whole PHPT series [n=503, aged 67.0 (61.0-74.0) years], 90% had low bone mineral density (BMD) and about 30% reported at least one fracture. Vertebral fractures were associated with older age and lower hypophosphatemia, while women with appendicular fractures were younger with less severe hypophosphatemia. Fractures were predicted by lumbar T-score. By using a clustering approach, we identified 4 different skeletal phenotypes (cluster, C): C1 (n=53) and C2 (n=172) included women with lumbar and femur neck osteopenia, with low prevalence of fractures (11.3%). Osteoporotic PHPT women were grouped in C3 (n=142) and C4 (n=136); all women in C4 experienced fractures, were older and more frequently affected with cardiovascular diseases. By contrast, women included in C3 never experienced fractures and had a lower body mass index (BMI), though they were characterized by severe reduction in bone mineral density (BMD) at both lumbar and femur sites. Ionized and total calcium, phosphate, 25hydroxyvitamin D levels, kidney function and stones prevalence (ranging 26.4-29.0%) were similar among clusters C1, C2 and C4, while unfractured women in C3 showed slightly higher ionized hypercalcemia and lower hypophosphatemia, higher hypercalciuria with a trend to develop more frequently kidney stones (38.7%) than women in the remaining clusters. Conclusions Skeletal involvement in women with PHPT presented heterogeneous phenotypes with different prevalence of fractures. Fractures were not related with PHPT severity, suggesting that other factors besides PHPT, such as age, BMI, lumbar and femur BMD, should be considered in the evaluation of bone involvement in postmenopausal women with PHPT.